La Investigación, Innovación y Extensión al servicio de la sociedad, en el marco de la Sexta Jornada de Apropiación Social del Conocimiento (2021)
Annually, the Technological University of Pereira has been carrying out some events in the line of Social Appropriation of Knowledge. This has been done through the research, innovation, and extension Vice Rectory, moreover, these sessions are framed within the institutional objective: “Define and direct the guidelines for the institutional research that strengthen the research groups and the Seedbeds, through the formation of researchers, the development of science, technology, and innovation projects or programs, as well as the generation of networks and strategic partnerships that contribute to the creation and appropriation of knowledge for the society”. Therefore, the 6th Social Appropriation of Knowledge event took place under the title of “The research, Innovation, and Extension at the service of society” which was constituted as an academic and institutional opportunity where the results of the research projects from the last 5 years were published. The results of this event revealed, once again, the high academic level in investigation development at the university. There were 11 articles divided into 6 fields: Health, Engineering, Technology, Education, Industrial Technology, and Art, in which the results obtained by the research projects from the investigation groups were shown, promoting a knowledge exchange from their authors whose intellectual formation is diverse. With this publication, as part of a permanent effort to socialize the knowledge, the university promotes the circulation of its professors, students, and general community voices, having in mind that knowledge must be transferred through different channels, strengthening the academy and society in general, according to the institutional mission that invites us to incentivize a research culture in the university community.